A single-flask synthesis of α-alkylidene and α-benzylidene lactones from ethoxyacetylene, epoxides/oxetanes, and carbonyl compounds. Issue 3 (20th January 2016) - Ng, Kevin; Tran, Vincent; Minehan, Thomas
Graphical abstract: Abstract: Low temperature treatment of (ethoxyethynyl)lithium with epoxides or oxetanes in the presence of BF3 ·OEt2, followed by addition of aldehydes or ketones and warming to room temperature, affords structurally diverse five- and six-membered α-alkylidene and α-benzylidene lactones (5 ) in good to excellent yields. This one-pot process, in which three new carbon–carbon bonds and a ring are formed, affords substituted α, β-unsaturated lactones of predominantly Z -configuration. The reaction likely occurs via alkyne–carbonyl metathesis of a hydroxy–ynol ether intermediate, acid-promoted alkene E - to Z -isomerization, and lactonization.